The World Bank Legal Review, Volume 5: Fostering Development through Opportunity, Inclusion, and Equity - Cissé, Hassane (World Bank, 2015)
This volume will explore the potentially transformative role of effective laws and legal institutions in providing people with more opportunity that is both inclusive and equitable.